2013
DOI: 10.3945/jn.112.173278
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Resistant Starch Prevents Urinary Excretion of 25-Hydroxycholecalciferol and Vitamin D-Binding Protein in Type 1 Diabetic Rats1,2

Abstract: Diabetes is a rapidly growing epidemic affecting millions of Americans and has been implicated in a number of devastating secondary complications. We previously demonstrated that type 2 diabetic rats exhibit vitamin D deficiency due to aberrant megalin-mediated endocytosis and excessive urinary excretion of 25-hydroxycholecalciferol (25D3) and vitamin D-binding protein (DBP). Here, we examined whether a model of type 1 diabetes [T1D; streptozotocin (STZ)-treated Sprague-Dawley rats] would similarly excrete abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 42 publications
2
34
1
Order By: Relevance
“…The higher plasma concentration of all fat-soluble vitamins and the majority of water-soluble vitamins in Zucker fa/fa rats compared to Long-Evans rats was clearly demonstrated in the PCA, despite similar energy intake between the two groups. This was an unexpected finding since the loss of both fat-soluble and water-soluble vitamins in urine has been demonstrated to be higher in rats with tubular injury (47,48) and since vitamin D insufficiency is highly prevalent in patients with chronic kidney disease (20) . Transport proteins for fat-soluble vitamins, including retinol-binding protein and vitamin D-binding protein, and water-soluble vitamins are filtered in the glomeruli and reabsorbed in the renal tubule or secreted in urine (49,50) .…”
Section: Discussionmentioning
confidence: 95%
“…The higher plasma concentration of all fat-soluble vitamins and the majority of water-soluble vitamins in Zucker fa/fa rats compared to Long-Evans rats was clearly demonstrated in the PCA, despite similar energy intake between the two groups. This was an unexpected finding since the loss of both fat-soluble and water-soluble vitamins in urine has been demonstrated to be higher in rats with tubular injury (47,48) and since vitamin D insufficiency is highly prevalent in patients with chronic kidney disease (20) . Transport proteins for fat-soluble vitamins, including retinol-binding protein and vitamin D-binding protein, and water-soluble vitamins are filtered in the glomeruli and reabsorbed in the renal tubule or secreted in urine (49,50) .…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, this new knowledge may be used in future dietary and therapeutic recommendations regarding the control of diabetes and its complications. For example, numerous recent reports have demonstrated that dietary resistant starch or probiotics have an important beneficial impact on diabetes and obesity (102,103), suggesting that intervention strategies that target the gut microbiota represent a viable approach for disease prevention or treatment.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Consumption of resistant starch can attenuate disruption of vitamin D homeostasis in type I diabetes through the rescue of megalin-mediated endocytosis in kidney in the absence of visible side effects [56]. …”
Section: Potential Side Effectmentioning
confidence: 99%